1998
DOI: 10.1074/jbc.273.19.11440
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of the Goodpasture Autoantigen to CD4 T Cells Is Influenced More by Processing Constraints Than by HLA Class II Peptide Binding Preferences

Abstract: Class II molecules are believed to influence immune responses by selectively binding antigen-derived peptides for recognition by T cells. In Goodpasture's (antiglomerular basement membrane) disease, autoimmunity to the NC1 domain of the ␣3-chain of type IV collagen (␣3(IV)NC1) is strongly associated with HLA-DR15. We have examined the influence of the peptide binding preferences of DR15 molecules on the selection of ␣3(IV)NC1-derived peptides displayed bound to DR15 molecules on the surface of ␣3(IV)NC1-pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 52 publications
3
52
1
Order By: Relevance
“…The recognition for P16 was identified to be associated with higher concentration of serum creatinine on diagnosis and was a poor prognostic indicator for renal outcome. We noticed that P16 contained one of the core sequences on a3(IV)NC1 that could be naturally processed and presented by antigen presenting cells (25,30). It is likely that these autoreactive B cells against P16 may serve as professional antigen presenting cells to stimulate autoreactive T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition for P16 was identified to be associated with higher concentration of serum creatinine on diagnosis and was a poor prognostic indicator for renal outcome. We noticed that P16 contained one of the core sequences on a3(IV)NC1 that could be naturally processed and presented by antigen presenting cells (25,30). It is likely that these autoreactive B cells against P16 may serve as professional antigen presenting cells to stimulate autoreactive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that P14 contained the core sequence with highest predicted binding affinity with HLA-DR15 (25,26), which was proven to be the genetic marker for susceptibility to anti-GBM disease. The finding that a mutual T and B cell epitope exists in human anti-GBM disease, in accordance with the results from animal models, favors the hypothesis that certain nephrogenic linear epitopes might initiate the disease by stimulating both humoral and cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…T cells from patients with acute disease react to a limited number of peptides of ␣3(IV)NC1 (␣3 71 to 90 and ␣3 131 to 150), suggesting that these are the likely natural immunodominant peptides (63). However, these are not the peptides that induce the strongest responses in T cells from patients with anti-GBM GN when presented by DR15 on Epstein-Barr virus-transformed human B cells, suggesting that factors other T cell receptor affinity determine selection of immunodominant autoreactive epitopes (64). The cytokine profile of autoreactive ␣3(IV)NC1 T cells from patients in the acute phase of the disease is Th1 predominant (producing IFN-␥); whereas during resolution of disease, IL-10 production is predominant (65).…”
Section: T Cells In Autoimmune Anti-gbm Gnmentioning
confidence: 99%
“…In the case of DR15-bearing individuals it is possible to test the hypothesis further because we have reported relative binding data for ␣3(IV)NC1 peptides, 15 which can be refined to identify probable epitopes using published binding algorithms.…”
Section: Highly Scissile Peptide Bonds Are Located Within the Epitopementioning
confidence: 99%